SENTENCE - Yayi, Sri (Fakultas Teknik Universitas Krisnadwipayana, 2015)
Sentence structure and the ability to develop into sentence. This research is bivariat with student’s mastery at sentence structure as independent variable. Sentence structure and the ability to developed sentence. Data were colected by instrument in the form of objective. The instrument validity, reliability, difficulty indices and discriminating indices were analysed. The data callected and analysed with the normality.